Design of a Continuous-Zoom 2D/3D Microscope with High Zoom Ratio and Full Field of View - Yangshen Gong; Fei Li; Jiebo Huang; Jiaying He; Feihong Yu; Tingyu Zhao (Photonics, 2024)
A four-group mechanically compensated continuous-zoom microscope is proposed and designed based on the theory of continuous zoom. The system addresses the limitations of traditional continuous-zoom microscopes, including a small zoom ratio, a short working distance, and the loss of details during 2D–3D switching. The system has a magnification of 0.6×~6.0× under two-dimensional observation, adapts to two-third-inch sensors, has a working distance of 130 mm, and adds a 360-degree rotatable beamsplitter for three-dimensional full-field-of-view observation. The magnification, numerical aperture, and sensor dimensions remain unchanged under both two-dimensional and three-dimensional observation. The design results demonstrate that the system is capable of achieving a high zoom ratio of 10× while maintaining a high level of imaging quality in both two-dimensional and three-dimensional modes. The MTF curves for each magnification are in close proximity to the diffraction limit, the spot diagrams are smaller than the airy disk range, and the zoom cam curves are smooth with no inflection points. Furthermore, the system negates the visual discrepancies and loss of detail that arise when switching observation modes due to alterations in system magnification and numerical aperture, thereby broadening the scope of applications for continuous-zoom microscopes.